Pandemic Causation and Protection. Health and More-Than-Human Relations in Phushar Village, Bhutan - Barbara Gerke; Yeshi Samdrup (Archivio Antropologico Mediterraneo)
This paper explores pandemic narratives in Phushar village, Western Bhutan, focusing on the interplay between humans, local deities (tsen, gyap), Buddhist protector and tutelary deities and public health measures during COVID-19. Villagers combined deity appeasement rituals with divinations and public health measures. Memories of past epidemics shaped adherence to quarantine, physical distancing and modern healthcare. The narratives reflect a shift from individual karmic disease causation to perceiving the pandemic as globalized lenchak (karmic retribution), emphasizing collective responsibility for the crisis. While deity protection was deemed successful during COVID-19, increasing climate challenges may reshape perceptions of ritual efficacy. This study contributes to understanding more-than-human relationships in disease causation and ritual disaster protection, showing how local traditions integrate broader moral and ecological frameworks.